Silicate nanoparticles by bioleaching of glass and modification of the glass surface - Kulkarni, Sneha; Syed, Asad; Singh, Sanjay; Gaikwad, Anil; Patil, Kashinath; Vijayamohanan, K.; Ahmad, Absar; Ogale, Satishchandra (Journal of Non-Crystalline Solids, 2008)
Bioleaching is examined as a low temperature (50 degrees C) soft chemical approach to nanosynthesis and surface processing. We demonstrate that fungus based bioleaching of borosilicate glass enables synthesis of nearly monodispersed ultrafine (similar to 5 +/- 0.5 nm) silicate nanoparticles. Using various techniques such as X-ray diffraction, X-ray photoelectron spectroscopy and FTIR we compare the constitution and composition of the nanoparticles with that of the parent glass, and establish the basic similarities between the two. The bioleaching process is shown to enhance the non-bridging oxygen component and correspondingly influence the Si-O-Si network. The root mean square roughness of glass surface is seen to increase from 1.27 nm for bare glass to 2.52 nm for 15 h fungal processed case, this increase being equivalent to that for glass annealed at 500 degrees C. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Bioglass; Biomaterials; borosilicates; narroparticles

Scaling behavior of resistive switching in epitaxial bismuth ferrite heterostructures - Rana, Abhimanyu; Lu, Haidong; Bogle, Kashinath A.; Zhang, Qi; Vasudevan, Rama; Thakare, Vishal; Gruverman, Alexei; Ogale, Satishchandra; Valanoor, Nagarajan (Advanced Functional Materials, 2014)
Resistive switching (RS) of (001) epitaxial multiferroic BiFeO3/La0.67Sr0.33MnO3/SrTiO3 heterostructures is investigated for varying lengths scales in both the thickness and lateral directions. Macroscale current-voltage analyses in conjunction with local conduction atomic force microscopy (CAFM) reveal that whilst both the local and global resistive states are strongly driven by polarization direction, the type of conduction mechanism is different for each distinct thickness regime. Electrode-area dependent studies confirm the RS is dominated by an interface mechanism and not by filamentary formation. Furthermore, CAFM maps allow deconvolution of the roles played by domains and domain walls during the RS process. It is shown that the net polarization direction, and not domain walls, controls the conduction process. An interface mechanism based on barrier height and width alteration due to polarization reversal is proposed, and the role of electronic reconstruction at the interface is further investigated.

Surfactant free gram scale synthesis of mesoporous Ni(OH)(2)-r-GO nanocomposite for high rate pseudocapacitor application - Singh, Upendra; Banerjee, Abhik; Mhamane, Dattakumar; Suryawanshi, Anil; Upadhyay, Kush Kumar; Ogale, Satishchandra (RSC Advances, 2014)
We report a single-step surfactant-free gram scale hydrothermal synthesis of mesoporous Ni(OH)(2) nanoparticles and the Ni(OH)(2)-reduced graphene oxide (Ni(OH)(2)-r-GO) nanocomposite. Interesting morphological features are noted. These nanomaterials are examined and compared as cathode materials for pseudo-capacitor application through detailed characterizations. A high specific capacitance (C-s) of 1538 F g(-1) is observed for Ni(OH)(2)-r-GO even at a high current density of 40 A g(-1), whereas at the same current rate, bare Ni(OH)(2) shows C-s of only 936 F g(-1).

Synthesis of an efficient heteroatom-doped carbon electro-catalyst for oxygen reduction reaction by pyrolysis of protein-rich pulse flour cooked with SiO2 nanoparticles - Gokhale, Rohan; Unni, SreeKuttan M.; Puthusseri, Dhanya; Kurungot, Sreekumar; Ogale, Satishchandra (Physical Chemistry Chemical Physics, 2014)
Development of a highly durable, fuel-tolerant, metal-free electro-catalyst for oxygen reduction reaction (ORR) is essential for robust and cost-effective Anion Exchange Membrane Fuel Cells (AEMFCs). Herein, we report the development of a nitrogen-doped (N-doped) hierarchically porous carbon-based efficient ORR electrocatalyst from protein-rich pulses. The process involves 3D silica nanoparticle templating of the pulse flour(s) followed by their double pyrolysis. The detailed experiments are performed on gram flour (derived from chickpeas) without any in situ/ex situ addition of dopants. The N-doped porous carbon thus generated shows remarkable electrocatalytic activity towards ORR in the alkaline medium. The oxygen reduction on this material follows the desired 4-electron transfer mechanism involving the direct reduction pathway. Additionally, the synthesized carbon catalyst also exhibits good electrochemical stability and fuel tolerance. The results are also obtained and compared with the case of soybean flour having higher nitrogen content to highlight the significance of different parameters in the ORR catalyst performance.

Single-layer graphene-assembled 3D porous carbon composites with PVA and Fe3O4 nano-fillers: an interface-mediated superior dielectric and EMI shielding performance - Rao, B. V. Bhaskara; Yadav, Prasad; Aepuru, Radhamanohar; Panda, H. S.; Ogale, Satishchandra; Kale, S. N. (Physical Chemistry Chemical Physics, 2015)
In this study, a novel composite of Fe3O4 nanofiller-decorated single-layer graphene-assembled porous carbon (SLGAPC) with polyvinyl alcohol (PVA) having flexibility and a density of 0.75 g cm(-3) is explored for its dielectric and electromagnetic interference (EMI) response properties. The composite is prepared by the solution casting method and its constituents are optimized as 15 wt% SLGAPC and 20 wt% Fe3O4 through a novel solvent relaxation nuclear magnetic resonance experiment. The PVA-SLGAPC-Fe3O4 composite shows high dielectric permittivity in the range of 1 Hz-10 MHz, enhanced by a factor of 4 as compared to that of the PVA-SLGAPC composite, with a reduced loss by a factor of 2. The temperature dependent dielectric properties reveal the activation energy behaviour with reference to the glass transition temperature (80 degrees C) of PVA. The dielectric hysteresis with the temperature cycle reveals a remnant polarization. The enhanced dielectric properties are suggested to be the result of improvement in the localized polarization of the integrated interface system (Maxwell-Wagner-Sillars (MWS) polarization) formed by the uniform adsorption of Fe3O4 on the surface of SLGAPC conjugated with PVA. The EMI shielding property of the composite with a low thickness of 0.3 mm in the X-band (8.2-12.4 GHz) shows a very impressive shielding efficiency of similar to 15 dB and a specific shielding effectiveness of 20 dB (g cm(-3))(-1), indicating the promising character of this material for flexible EMI shielding applications.

Synthetic manipulation of hybrid perovskite systems in search of new and enhanced functionalities - Naphade, Rounak; Nagane, Satyawan; Bansode, Umesh; Tathavadekar, Mukta; Sadhanala, Aditya; Ogale, Satishchandra (ChemSusChem, 2017)
Over the past few years the organic-inorganic hybrid perovskite systems have emerged as a promising class of materials for photovoltaic and electroluminescent thin-film device applications, in view of their unique set of tunable optoelectronic properties. Importantly, these materials can be easily solution-processed at low temperatures and as such are amenable to facile molecular engineering. Thus, a variety of low-dimensional forms and quantum structures of these materials can be obtained through strategic synthetic manipulations through small molecule incorporation or molecular ion doping. In this Minireview, we specifically focus on these approaches and outline the possibilities of utilizing these for enhanced functionalities and newer application domains.